ZmGCT1/2 negatively regulate drought tolerance in maize by inhibiting ZmSLAC1 to maintain guard cell turgor - Zhenkai Feng; Huiying Li; Zhihui Sun; Jinkui Cheng; Deping Hua; Yu Wang; Junsheng Qi; Shuhua Yang; Zhizhong Gong (Proceedings of the National Academy of Sciences, 2025)
Stomata, which are essential for the exchange of CO 2 and water vapor between plant leaves and the atmosphere, are regulated by a variety of environmental and internal factors. In this study, we identified and characterized two genes, Guard Cell Turgor Maintaining 1 ( GCT1 ) and its closest homolog GCT2 , which encode rapidly accelerated fibrosarcoma (RAF)-like protein kinases that play a critical role in maintaining guard cell turgor in Zea mays . We found that overexpression of ZmGCT1 and ZmGCT2 confers resistance to abscisic acid (ABA)-promoted stomatal closure, whereas the zmgct1 zmgct2 double loss-of-function mutants exhibit a loss of guard cell turgor, resulting in nearly closed stomata even under favorable growth conditions. A dominant mutation, zmgct1-9D , which lacks nine amino acids including T80, retains its kinase activity and plasma membrane localization but displays insensitive to ABA-, CO 2 -, Ca 2+ -, or H 2 O 2 -promoted stomatal closure. ABA-activated ZmSnRK2.8/9 phosphorylates ZmGCT1 at T80, reducing its plasma membrane localization. Intriguingly, the ZmSnRK2.10 or ZmSLAC1 mutant can suppress the reduced turgor phenotype in guard cells of the zmgct1 mutant. Furthermore, ZmGCT1 phosphorylates the penultimate threonine residue (T573) of ZmSLAC1, inhibiting both the constitutively active ZmSLAC1 and ZmSnRK2.8-activated ZmSLAC1 in Xenopus laevis oocytes, a process dependent on ZmGCT1 kinase activity. These findings suggest that ZmGCT1 and ZmGCT2 directly inhibit ZmSLAC1 to maintain guard cell turgor under favorable growth conditions, while ABA treatment alleviates this inhibition primarily by reducing ZmGCT1’s plasma membrane localization. This study provides mechanistic insights into the regulation of stomatal movement by ZmGCT1/2 kinases under both favorable and stress conditions.